Programación y modelos de ingeniería ambiental - Bonilla Domínguez, Ubaldo; Cuevas Renaud, Baltazar; Zepeda Porras, Francisco (My University, 1976)
Determine the existing installations for the Project are. May involve field measurements or determination of land uses in the area. Note any unique noise sources in the area, or any unique places where noise levels must be minized
Keywords: contaminación atmosférica; contaminación bacteriana; contaminación térmica; agua; desechos solidos